PERANAN ORANG TUA DALAM MEMBINA SIKAP (ATTITUDE) ANAK DI DESA HILIGITO KECAMATAN FANAYAMA TAHUN 2020 - Fincensius Luahambowo (Civic Society Research and Education: Jurnal Pendidikan Pancasila dan Kewarganegaraan, 2020)
The role of parents is the cooperation of both parents (father and mother) is a big influence in educating and disciplining children. The role of parents is to strive for each child to have a good attitude, high intelligence, and skills that benefit everyone. This research aims to find out how the role of parents in fostering bad child attitudes, especially in Hiligito Village, Fanayama Subdistrict. The location of this study was carried out in Hiligito Village of Fanayama District of South Nias Regency. The type of research used in this research is a type of qualitative research with ethnographic approach. The data collection techniques carried out in this study are (1) observations; (2) interview; and (3) documents. The results of this study showed that (1) the attitude of children in Hiligito Village of Fanayama Subdistrict is less good because it has various factors that can affect it, namely internal and external factors. Internal factors are the attitudes of children that arise from themselves without outside influence or others. While external factors are factors that affect the attitude of children from outside himself; (2) The role of parents in fostering children's attitudes in Hiligito Village of Fanayama Subdistrict consists of two forms, namely, repressively and preventively. Coaching in a repressive form is the action that parents take on their children in educating their children in a better direction. While coaching in the form of preventive is the prevention of children so as not to fall into bad deeds. Some of the suggestions submitted by researchers, namely (1) parents should carry out their actual functions and roles towards their children, so that their children have character and morality; (2) Every circle of the village child should be equipped, guided and directed, so that every village child has a good mindset and tolerance.